0.90x+.05(2-x)=.10(-67)

Simple and best practice solution for 0.90x+.05(2-x)=.10(-67) equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for 0.90x+.05(2-x)=.10(-67) equation:


Simplifying
0.90x + 0.05(2 + -1x) = 0.10(-67)
0.90x + (2 * 0.05 + -1x * 0.05) = 0.10(-67)
0.90x + (0.1 + -0.05x) = 0.10(-67)

Reorder the terms:
0.1 + 0.90x + -0.05x = 0.10(-67)

Combine like terms: 0.90x + -0.05x = 0.85x
0.1 + 0.85x = 0.10(-67)

Multiply 0.10 * -67
0.1 + 0.85x = -6.7

Solving
0.1 + 0.85x = -6.7

Solving for variable 'x'.

Move all terms containing x to the left, all other terms to the right.

Add '-0.1' to each side of the equation.
0.1 + -0.1 + 0.85x = -6.7 + -0.1

Combine like terms: 0.1 + -0.1 = 0.0
0.0 + 0.85x = -6.7 + -0.1
0.85x = -6.7 + -0.1

Combine like terms: -6.7 + -0.1 = -6.8
0.85x = -6.8

Divide each side by '0.85'.
x = -8

Simplifying
x = -8

See similar equations:

| (5t^2-t-7)(2t^2+5t-1)= | | 14-3/5= | | 4(-2r+3)-2(1-6r)= | | 3x+7=49 | | (8t^2-t-5)(4t^2+8t-1)= | | x^2-13y^2=101 | | 130=14a-10 | | 1.3-5=5.4 | | 16a+10=90 | | -3x-4=-22 | | 5x-10=50-x | | 5(x-2)-8x=-24 | | 0.5s=10 | | (4x-5)(x^2-3x+3)= | | 6x^2-16x+5=0 | | (3x-5)(x^2-2x+6)= | | 4x-1=20-30 | | v^2-v-42= | | absolute(x^2-1)=0 | | 4x-1=2-30 | | 3(u-8)-8u=6 | | 6x-10=100+2x | | k+7=-16 | | 2(3n+2)+2(n+4)=36 | | 126=63n | | 3+3=72 | | 6(x-3)=72/12 | | 3(5x-2)-5(3x-1)=0 | | -9n+12=-5n-12 | | X^2+7x=8x^2 | | -2y-8=3y+7 | | 4-4=14x+4x |

Equations solver categories